Efektifitas Implementasi Contractor Safety Management System (CSMS) Terhadap Penurunan Tingkat Kecelakaan Kerja Di PT X - Pradani, Midyana Restu; Maharani, Maya Dewi Dyah; Ramli, Soehatman (LPPM Akademi Minyak dan Gas Balongan Indramayu, 2021)
Contractor Safety Management System (CSMS) is a documentation of a control mechanism in the form of guidelines to ensure business standards in managing the HSE performance of contractors. PT X is a company engaged in services in the oil and gas sector, which has a high risk in every day-to-day operational activity of having an accident with lost working hours (LTI) caused by contractors. This study aims to determine whether the CSMS implementation is effective enough to reduce the level of accidents at PT X. This research is a descriptive type of research or a qualitative approach evaluation study with the method of data analysis carried out by the Literature Tracing Method which produces CSMS Implementation Data & Accident Data and interviews. Experts then structured CSMS problems into hierarchical institutional elements and sub-elements using the Interpretative Structural Modeling (ISM) Method. The results showed that the implementation of CSMS at PT X was quite effective in reducing the number of accidents at PT X but for the implementation of this CSMS cycle must be carried out according to the CSMS guidelines at PT X and with consistency at each stage so that no negligence impacted accidents for contractors carrying out contract work at PT X. Keywords: Contractor, CSMS